2019
DOI: 10.1080/09500693.2019.1660927
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between instructional practices and science achievement in an inquiry-based learning environment

Abstract: This study investigates the discrete effects of inquiry-based instructional practices that described the PISA 2015 construct 'inquiry-based instruction' and how each practice, and the frequency of each practice, is related to science achievement across 69 countries. The data for this study were drawn from the PISA 2015 database and analysed using hierarchical linear modelling (HLM). HLMs were estimated to test the contribution of each item to students' science achievement scores. Some inquiry practices demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 46 publications
3
52
0
11
Order By: Relevance
“…Secondly, there is the need to address the tradeoffs between enhancing students' science achievement and enabling students to acquire process skills such as scientific inquiry and informed views of NOS. In a study that involved 69 countries which participated in the 2015 Program for International Students Assessment (PISA), Cairns (2019) found that the aspect of open inquiry such as students designing their own experiments and having a debate about science investigation were negatively correlated with science achievements. Meanwhile, students arguing about science questions and drawing conclusions were not correlated with achievement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, there is the need to address the tradeoffs between enhancing students' science achievement and enabling students to acquire process skills such as scientific inquiry and informed views of NOS. In a study that involved 69 countries which participated in the 2015 Program for International Students Assessment (PISA), Cairns (2019) found that the aspect of open inquiry such as students designing their own experiments and having a debate about science investigation were negatively correlated with science achievements. Meanwhile, students arguing about science questions and drawing conclusions were not correlated with achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, students arguing about science questions and drawing conclusions were not correlated with achievement. Instead, teacher-directed items such as teacher explaining how a scientific idea is applied were related to gains in science achievement (Cairns, 2019). Therefore, given that science teachers in Tanzania must aspire to raise students' science achievements, formal arrangements such as having few class hours dedicated to IBST and NOS activities each week can help to focus on these process skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Student activity sheets also encourage student activity in remembering, understanding, applying, and analyzing. Student worksheets can also help provide instruction on what students should do (Cairns, 2019). Thus, learning tools that are systematic and relevant in the preparation, process, and competency objectives will have consistent results on other topics.…”
Section: Discussionmentioning
confidence: 99%